Community-based disaster response teams for vulnerable groups and developing nations : implementation, training, and sustainability : a thesis presented in partial fulfilment of the requirements for the degree of Master of Emergency Management at Massey University, Wellington, New Zealand - Cull, Paul (Massey University, 2019)
Bystanders are often the first to respond to disasters and, for this reason, Community-Based Disaster Response Teams (CBDRTs) should be established in vulnerable communities. The literature review examines Disaster Risk Reduction initiatives and identifies that there is little information available regarding strategies and training curriculum that could be used to establish and maintain CBDRTs in developing nations and with vulnerable groups. The three research questions for this investigation ask how CBDRT courses could be adapted for these communities, what topics and activities would be most useful for such training, and how the teams could be established and maintained. The research objectives are to identify strategies that could be used to train CBDRT groups in these contexts, to propose an outline for a basic training course, and to describe techniques that could contribute to the sustainability of these teams. Research was conducted with CBDRTs in developing nations using a mixed methods methodology with the United States Federal Emergency Management Agency’s (FEMA) Community Emergency Response Team (CERT) programme being employed as a case study. Quantitative data was obtained from a questionnaire completed by CERT course graduates, and qualitative information was acquired from key informant interviews. After a review of the CERT programme that discusses its history, curriculum, success stories, and potential pitfalls, the data collected is presented through statistical analysis of the questionnaire replies and thematic analysis of the interview transcripts. Suggested CBDRT training strategies are creating courses for adolescents, modifying the material for non-literate learners, and providing additional practical activities. Recommendations for establishing programmes include developing teams for young people, cooperating with Community-Based Organisations to solve existing problems, and offering CBDRT training in the post-disaster environment. Techniques for maintaining the teams involve developing leadership, creating support networks, and cultivating partnerships with local authorities. The final conclusion is that the CERT model could be used as the basis for an international CBDRT training programme, although it would require adaption of the course content and presentation style.
Keywords: Disaster relief; Emergency management; Developing countries; Citizen participation; Study and teaching (Continuing education); Community Emergency Response Team (U.S.); 920407 Health Protection and/or Disaster Response